Delay of initial radioactive iodine therapy beyond 3 months has no effect on clinical responses and overall survival in patients with thyroid carcinoma: A cohort study and a meta‐analysis. (18th February 2022) - Cheng, Fang; Xiao, Juan; Huang, Fengyan; Shao, Chunchun; Ding, Shouluan; Yun, Canhua; Jia, Hongying
Abstract: Background: More than a third of thyroid carcinoma (TC) patients require treatment with radioactive iodine (RAI), but the timing of initial RAI therapy after thyroidectomy remains controversial. Methods: We included 1224 differentiated thyroid carcinoma (DTC) patients during 2015–2019, divided them into the early (≤3 months) and the delayed (>3 months) groups based on the interval between surgery and the initial RAI. Clinical outcomes were assessed within 6–8 months of treatment with RAI, including excellent response (ER), indeterminate response (IDR), biochemical incomplete (BIR) and structural incomplete response (SIR). Further transformed them into dichotomous outcomes, we therefore introduced the ordered/binary logistic regression to assess the relation of time interval and quaternary/dichotomous outcomes, respectively. Finally, we conducted a meta‐analysis for cohort study to investigate the effect of timing of RAI therapy on the prognosis of TC. Results: Delay RAI therapy beyond 3 months reduced the IR (BIR + SIR) rate in the present cohort study ( RR = 0.67, 95% CI: 0.49–91). Following meta‐analysis including 38, 688 DTC patients confirmed these results ( RR = 0.77, 95% CI: 0.66–0.91), further revealed the duration of treatment does not influence OS (pooled RR = 1.05, 95% CI: 0.83–1.33). Conclusion: Delayed initial RAI therapy beyond 3 months but no later than 6 months did not impair the prognosis of TC. Abstract : We conducted a cohort study to investigate whether the time of initial radioactive iodine (RAI) administration would affect the clinical responses, and incorporate these results into the current body of evidence by performing meta‐analysis. Providing a solid theoretical basis for the revision of clinical guidelines.